APE1/Ref-1 Role in Inflammation and Immune Response - Oliveira, Thais Teixeira; Coutinho, Leonam Gomes; de Oliveira, Laysa Ohana Alves; Timoteo, Ana Rafaela de Souza; Farias, Guilherme Cavalcanti; Agnez-Lima, Lucymara Fassarella (Frontiers in Immunology, 2022)
Apurinic/apyrimidinic endonuclease 1/redox effector factor 1 (APE1/Ref-1) is a multifunctional enzyme that is essential for maintaining cellular homeostasis. APE1 is the major apurinic/apyrimidinic endonuclease in the base excision repair pathway and acts as a redox dependent regulator of several transcription factors, including NF-κB, AP-1, HIF-1α, and STAT3. These functions render APE1 vital to regulating cell signaling, senescence, and inflammatory pathways. In addition to regulating cytokine and chemokine expression through activation of redox sensitive transcription factors, APE1 participates in other critical processes in the immune response, including production of reactive oxygen species and class switch recombination. Furthermore, through participation in active chromatin demethylation, the repair function of APE1 also regulates transcription of some genes, including cytokines such as TNFα. The multiple functions of APE1 make it an essential regulator of the pathogenesis of several diseases, including cancer and neurological disorders. Therefore, APE1 inhibitors have therapeutic potential. APE1 is highly expressed in the central nervous system (CNS) and participates in tissue homeostasis, and its roles in neurodegenerative and neuroinflammatory diseases have been elucidated. This review discusses known roles of APE1 in innate and adaptive immunity, especially in the CNS, recent evidence of a role in the extracellular environment, and the therapeutic potential of APE1 inhibitors in infectious/immune diseases.